THE PERILS OF BEING A MALE PRIMARY/JUNIOR TEACHER: VULNERABILITY AND ACCUSATIONS OF INAPPROPRIATE CONTACT WITH STUDENTS - Parr, Michael; Gosse, Douglas (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2012)
There is a perceived shortage of male teachers in education, particularly at the primary/junior (P/J) level where male teachers in Canada account for a dwindling minority. Included among the many factors inhibiting males from becoming P/J teachers are perceptions that males might be unduly vulnerable to false accusations of inappropriate conduct with pupils, frequently of a sexual nature. This paper highlights findings of research exploring the experiences of male P/J teachers in Ontario. Results of an online survey completed by 223 male P/J teachers are discussed; 28 of these teachers reported they had been suspected of having had inappropriate contact with pupils and wrote online comments outlining their experience. The findings are discussed in the context of what it means to be a male assuming a non-traditional role of working with young children in today’s milieu. LES RISQUES D'ETRE ENSEIGNANT MALE AUX NIVEAUX PRIMAIRES ET JUNIORS: LES VULNERABILITES ET ACCUSATIONS POSSIBLES DE CONTACT INAPPROPRIE AVEC LES ELEVES. Il est perçu au Canada, qu'il existe une pénurie enseignants masculins, particulièrement aux niveaux primaires et juniors. Parmi les facteurs qui les empêchent de considérer la profession, est le fait qu'ils se sentent vulnérables. Cette présentation vise à souligner une recherche faite auprès de 223 enseignants masculins en Ontario de niveau primaire et junior. Cette enquête électronique démontre que 28 parmi eux ont déjà été soupçonnés d’un contact inapproprié et discutent des circonstances et les répercussions de ces commentaires. Les résultats de cette recherche sont présentés dans le contexte des implications d'être enseignant masculin travaillant avec de jeunes enfants dans un milieu de travail non traditionnel.